Environmental mutagenesis and use of biomarkers in cancer risk prediction - Cuenca, Patricia (2004)
The field of environmental mutagenesis or toxicology genetics aims to study the genetic damage that leads to mutations produced by physical, chemical and biological agents, to identify these agents and analyze their interactions and ways of action. There are enough experimental and epidemiological evidences implicating mutations in oncogenes, tumor suppressor genes and DNA repair genes as determinants in the onset and progression of the neoplastic process. A valuable tool in public and occupational health is the monitoring of populations exposed to potentially hazardous agents. The objective is to protect the health and quality of life of high risk groups on account of the nature of the agents of exposure. Monitoring of genotoxic effects in exposed populations as well as the analysis of susceptibility polymorphism are visualized as key tools in the realm of future public and occupational health in order to prevent the occurrence of environmental and specially occupational origin of tumors. This paper reviews the main concepts concerning this issue and refers to studies on the subject in Costa Rica